The Role of Influencers in Increasing Purchasing Decisions with Variable Trust as an Intervening Variable (Study on LazisMU Donors in the Ex. Karesidenan Besuki Region): Peran Influencer Dalam Meningkatkan Keputusan Pembelian Dengan Variable Kepercayaan Sebagai Variabel Intervening (Studi Pada Donatur LazisMU Wilayah Eks. Karesidenan Besuki) - Qomariah, Nurul; Khamil, Abdul; Kamil, Ibrahim; Cahyono, Dwi; Sanorsa, Abadi; Nursaid, Nursaid (Universitas Muhammadiyah Sidoarjo, 2024)
Philanthropy is social generosity that is programmed and aimed at alleviating social problems in society (such as poverty). LazisMU is one of the institutions that carry out philanthropic activities in overcoming social problems in society. This study aims to analyze and test the role of influencers on people's decisions to become donors with trust as an intervening variable in LazisMU charitable institutions in the Ex. Karesidenan Besuki region which includes Jember, Banyuwangi, Situbondo and Bondowoso. The research questionnaire was distributed to donors as many as 250 respondents. The sample size of 250 respondents was obtained from the Slovin formula with a population of 3635 donors. Hypothesis testing was conducted to answer the research hypothesis that had been compiled previously. The results of statistical analysis show that influencer variables have a positive and significant influence on the decisions of LazisMU donors. Trust from donors has a positive impact on the decisions of LazisMU donors. The trust variable becomes an intermediary variable for the influence of influencers on the decision to become a donor to LazisMU.